Wear and corrosion resistance enhancement of chromium surfaces through graphene oxide coating - Ozkan, Dogus; Erarslan, Yaman; Kincal, Cem; Gurlu, Oguzhan; Yagci, M. Baris (ELSEVIER SCIENCE SA, 2020)
Corrosion and wear protection of metals are crucial for all industrial applications. Graphene oxide (GO) is a chemically modified form of graphene and is highly promising for corrosion inhibition. Although corrosion protection of metal surfaces by the use of graphene oxide has been well investigated, anti-wear reduction of graphene oxide has not been studied especially under lubricated condition. In this work, Cr coated steel ring was coated with GO by atmospheric pressure chemical vapor deposition that hasn't been reported in the literature yet. The corrosion resistance of the coatings was evaluated by potentiodynamic polarization, immersion tests and the wear behavior of the coatings was investigated under lubricated conditions. Here we show that GO coated piston rings showed excellent corrosion resistance at extreme corrosive media. Our results also show that GO reacts with ZDDP and forms tribofilm that provides additional wear resistance to the ring, which resulted in very effective wear protection because of no wear scar observation on the ring surface.
Keywords: Graphene oxide; Piston rings; Corrosion rate; Raman analysis; Boundary lubrication condition; The coefficient of friction; ANTICORROSION PERFORMANCE; FUNCTIONALIZED GRAPHENE; COMPOSITE COATINGS; FRICTION; FILMS; TRIBOLOGY; THICKNESS; BEHAVIOR; STEEL; Materials Science; Physics